Peroxo Compounds of Vanadium(V) and Niobium(V) as Potent Inhibitors of Calcineurin Activity towards RII‐Phosphopeptide. Issue 21 (25th July 2017) - Saikia, Gangutri; Gogoi, Sandhya Rani; Boruah, Jeena Jyoti; Ram, Babul Moni; Begum, Pakiza; Ahmed, Kabirun; Sharma, Mitu; Ramakrishna, Gayatri; Ramasarma, Tangirala; Islam, Nashreen S.
Abstract: Calcineurin (CN) is a major calmodulin binding serine/threonine phosphatase which plays a crucial role in numerous mammalian signal transduction pathways. Calcineurin inhibitors represent a valuable tool for elucidating CN dependent cellular processes. The present work deals with the synthesis and comprehensive characterization of a new polymer anchored peroxo niobium complex, [Nb2 (O2 )6 (carboxylate)2 ]‐PA(Nb2 ) [PA=poly(sodium acrylate)], and identification of a set comprising of neat homoleptic as well as polymer immobilized peroxo complexes of vanadium(V) and niobium(V) as potent CN inhibitors. The in‐vitro effect of the complexes on calmodulin mediated dephosphorylation activity of CN was investigated using a physiological substrate of calcineurin, RII‐phosphopeptide as well as a non‐protein substrate p‐ nitrophenyl phosphate (p ‐NPP). Enzyme kinetic analysis data revealed that the compounds inhibit function of CN via uncompetitive pathway with K i values ranging between 1–3 μM, suggesting the formation of an enzyme‐inhibitor‐substrate complex during the course of inhibition. Abstract : Free monomeric and polymer anchored peroxo compounds of vanadium and niobium were synthesized and screened for their in‐vitro effect on calmodulin mediated dephosphorylation of RII‐phosphopeptide by calcineurin. Kinetic analysis show that the compounds are potent uncompetitive inhibitors of calcineurin with K i values ranging between 1–3 μ M suggesting the formation of an enzyme‐inhibitor‐substrate complex during inhibition.